Performance of soybean under poplar based agroforestry system in Terai region - Pandey, Raju; Dubey, Asutosh; Tewari, Lakshmi; Kumar, Amit; Kumar, Deepak; Sharma, Nidhi; Tewari, Salil K. (Indian Journal of Agroforestry, 2020)
Soybean is one of the major crops grown under poplar based agroforestry system in kharif season in northern India. However, reduction in yield of soybean over period of time under close canopy and partially open conditions in comparison to open becomes major factor for its adaptation. In present study, performance of soybean (variety PS-1347) was quantified in three and four years aged 18 clones of poplar under the tree, partially open and open systems in terai region of Uttarakhand. Germination count, plant height and dry matter accumulation showed significant variations under tree, partially open and open conditions. Growth and yield parameters were significantly higher in open condition than partially open and under the tree canopy.